PENGARUH HIDROTERAPI DAN MUSIK ALAM TERHADAP KUALITAS TIDUR PASIEN YANG MENJALANI KEMOTERAPI KANKER PAYUDARA - Diah Tias Avika; Anis Ardiyanti; Diffa Risqa Arisdiani (Tahta Media Group, 2024)
Breast cancer refers to the cellular malignant growth in breast tissue. Chemotherapy is an applicable treatment for breast cancer but this treatment causes sleeping problems as a side effect. Hydrotherapy and natural music are non-pharmacological methods to manage sleep problems. This quasi-experimental research determines the effects of hydrotherapy and natural music therapy on the quality of sleep of patients receiving breast cancer chemotherapy by applying One Group Pretest and Posttest. The research took 43 sample people using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The survey results revealed that 43 respondents, primarily aged 46 to 55 (23 respondents or 53.5%), 16 respondents with primary education (37.2%), and 32 unemployed respondents (74.4%). Most respondents received chemotherapy at Dr. Kariadi's hospital and had poor sleeping quality before the intervention. After the intervention, 32 respondents had excellent sleeping quality (74.4%). Wilcoxon's statistical results found the influence of hydrotherapy and natural music on the sleeping of patients receiving breast cancer chemotherapy at Dr. Kariadi's Hospital. The P-value value is 0.000 lower than 0.05, accepting Ha and rejecting Ho. The results also recommend the management of the intervention at the same room temperature.